Antiangiogenic proteins require plasma fibronectin or vitronectin for in vivo activity - Yi, Ming (National Academy of Sciences, 2003)
Fragmentation of various extracellular matrix and blood proteins generates antiangiogenic substances that are physiological regulators of angiogenesis. Some of these compounds are in clinical trials as inhibitors of tumor angiogenesis. Anastellin, an antiangiogenic protein fragment derived from fibronectin, was unable to inhibit matrigel plug angiogenesis in mice that lack plasma fibronectin. Anastellin was fully active in mice that are null for vitronectin, which, like fibronectin, is a major adhesion protein in the blood. An antiangiogenic form of antithrombin showed the opposite pattern. The activity of endostatin was impaired in both fibronectin- and vitronectin-deficient mice. These results suggest a shared mechanism of action for antiangiogenic factors derived from extracellular matrix and plasma proteins: these factors form complexes with adhesion proteins in plasma to create an active antiangiogenic substance.